Decidualized Ovarian Mass Mimicking Malignancy - Lufee Wong; Vola Botolahy; Thibault Carteret; Marion Marty; Jean-Luc Brun (Case Reports in Obstetrics and Gynecology)
Deciduosis classically occurs in the context of known endometriosis in the pelvis, most commonly in the ovaries, but also in the peritoneum. However, ovarian deciduosis outside the context of endometriosis is rare and makes diagnosis difficult, especially as the sonographic appearance suggests a malignant process. We report a case of decidualized ovarian mass in a patient without prior history of endometriosis that mimicked an ovarian malignancy. MRI may be a useful imaging modality to monitor these lesions and guide management. Consultation with a multidisciplinary team accustomed to such conditions will help to tailor the management to each individual.